Erratum: DARIO R. FAUSTINO-FUSTER, JEISSON A. LÓPEZ-CASTAÑO, JHONATAN M. QUIÑONES & VANESSA MEZA-VARGAS (2024) Increasing the species diversity of the monotypic genus Pariolius Cope 1872 (Siluriformes: Heptapteridae) after more than 150 years. Zootaxa, 5433 (3): 389–403. - Faustinofuster, Dario R.; Lópezcastaño, Jeisson A.; Quiñones, Jhonatan M.; Mezavargas, Vanessa (Zootaxa, 2024)
N/A